Portas lógicas totalmente ópticas baseado em interferômetro de Michelson com amplificador óptico semicondutor - OLIVEIRA, Jackson Moreira (Universidade Federal do Pará, 2018)
In this work, proposes all-optical logic gates device structure based on a Michelson interferometer (MI) composed of semiconductor optical amplifier (SOA) forming a structure of SOA-MI logic devices with symmetrically identical Fiber Bragg Grating (FBG) at the output of each of its arms, for numerical simulation of the all-optical AND, OR and NOR logic gates of two binary input signals with different bit numbers using the cross-gain modulation (XGM) technique at 10 Gb/s bit rate and filter bandwidth at 10, 20 and 40 GHz using OptiSystem 15.0 software by OptiWave Corporation, to demonstrate and extract simple design rules for high-speed optical processing and analysis of non-linear SOA-induced properties. In addition, this work includes the study of the effect of bandwidth and number of bits on received power, minimum bit error rate (BER), maximum quality factor (Q-factor), Optical Signal to Noise Ratio (OSNR) and optical spectrum, which demonstrates high-speed gates and performance. Were run the SOA-MI-based logic gates with some parameters and the results can demonstrate a structure of high-performance optical logic devices with high speed.